2019
DOI: 10.3390/w11061141
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Chloramphenicol on Commercial and Modified Activated Carbons

Abstract: The aim of the study was to evaluate the possibility of applying commercial activated carbons currently used in water treatment plants and modified carbon at 400 and 800 °C in the atmosphere of air, water vapour and carbon dioxide to remove chloramphenicol. Adsorption kinetics was examined for solutions with pH of 2–10. Adsorption kinetics were determined for the initial concentration of chloramphenicol of 161 mg/dm3 and the adsorption isotherm was determined for the concentrations of 161 to 1615 mg/dm3. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…For instance, activated carbon from coconut shell achieved a specific surface area of 1108.4 m 2 g −1 , and pore volume of 0.4323 cm 3 g −1 , approximately 2 times larger than wood biochar (Herath et al 2019 ). Lach ( 2019 ) demonstrated that pores and surface area of activated carbons are directly proportional to their adsorption performance. Indeed, they found activated carbon with the largest specific surface of 1692 m 2 g −1 , and pore volume of 2.103 cm 3 g −1 exhibited the highest chloramphenicol adsorption capacity of 214.91 mg g −1 .…”
Section: Removal Of Chloramphenicolmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, activated carbon from coconut shell achieved a specific surface area of 1108.4 m 2 g −1 , and pore volume of 0.4323 cm 3 g −1 , approximately 2 times larger than wood biochar (Herath et al 2019 ). Lach ( 2019 ) demonstrated that pores and surface area of activated carbons are directly proportional to their adsorption performance. Indeed, they found activated carbon with the largest specific surface of 1692 m 2 g −1 , and pore volume of 2.103 cm 3 g −1 exhibited the highest chloramphenicol adsorption capacity of 214.91 mg g −1 .…”
Section: Removal Of Chloramphenicolmentioning
confidence: 99%
“…This fact increases the chance of contact between chloramphenicol and the absorbent, which also increases the removal efficiency (Chitongo et al 2019 ). For example, Lach ( 2019 ) investigated the removal efficiency of chloramphenicol by granular activated carbons. The outcomes proved that the maximum removal efficacy of chloramphenicol was 99% at a dose of 8 g L −1 , compared with 36% of that at a dose of 1 g L −1 .…”
Section: Removal Of Chloramphenicolmentioning
confidence: 99%
“…An FTIR Spectrum 2000 spectrometer (Perkin-Elmer) was used to determine the FTIR transmission spectra (Lach, 2019).…”
Section: Activated Carbonsmentioning
confidence: 99%
“…Studies have shown that the use of adsorption technique by activated carbon is very effective in the disposal of many organic pollutants such as dyes, pesticides and aromatic compounds generally (8) . However, there are two problems facing this promising technique: the first problem is the high production cost of activated carbon and needed for continuous regeneration process, in addition to the part loss of this material during each regeneration process, while the second problem relates to the difficulty of sediments disposal from the surface of activated carbon or other adsorbents (9) . This led the researchers to seek for other sources to be used as adsorbents or raw materials in the preparation of activated carbon from them and also so that the amount of remaining materials are small (10) .…”
Section: Introductionmentioning
confidence: 99%